3D Reconstitution of the Neural Stem Cell Niche: Connecting the Dots - Ioannidis, Konstantinos; Angelopoulos, Ioannis; Gakis, Georgios; Karantzelis, Nikolaos; Spyroulias, Georgios A.; Lygerou, Zoi; Taraviras, Stavros (Frontiers in Bioengineering and Biotechnology, 2021)
Neural stem cells (NSCs) are important constituents of the nervous system and they become constrained in two specific regions during adulthood: the subventricular zone (SVZ) and the subgranular zone (SGZ) of the dentate gyrus in the hippocampus. The SVZ niche is a limited space zone where NSCs are situated, comprised by growth factors and Extracellular Matrix (ECM) components that shape the microenvironment of the niche. The interaction between ECM components and NSCs regulates the equilibrium between self-renewal and differentiation. To comprehend the niche physiology and how it controls NSCs behavior, it is fundamental to develop in vitro models that resemble adequately the physiological conditions present in the neural stem cell niche. These models can be developed from a variety of biomaterials, along with different biofabrication approaches that permit the organization of neural cells into tissue-like structures. This review intends to update the most recent information regarding the SVZ niche physiology and the diverse biofabrication approaches that have been used to develop suitable microenvironments ex vivo that mimic the NSC niche physiology.